Accounting for investments in Singapore. - Foo, Jinny Chen Nee. (2008)
This project is concerned with how to help companies better understand the requirements that they faced in accounting for their various forms of investments. Thus, this project will provide a description of the prescribed or recommended practices listed in the Singapore Accounting Standards for investments in properties, current investments, long-term investments, subsidiaries, associates and joint ventures.